Comparing College Students’ Motivation Trajectories Before and During COVID-19: A Self-Determination Theory Approach - Corpus, Jennifer Henderlong; Robinson, Kristy A.; Liu, Zhaoying (Frontiers in Education, 2022)
College students’ retrospective reports commonly indicate motivational declines associated with the COVID-19 pandemic. Using Self-Determination Theory, the present study provided a more nuanced examination of the pandemic’s motivational effect by measuring actual change in six distinct types of motivation. We compared motivation trajectories from the first to the fourth year of college for two cohorts of students, with the fourth-year measurement taken prior to the pandemic in one cohort (n = 206) but during the pandemic in the other (n = 270). Compared to the pre-pandemic cohort, the COVID cohort showed sharper declines in identified and intrinsic motivation but no differences in controlled motivation or amotivation. Motivational declines associated with the COVID-19 pandemic appeared to be both real and specific to autonomous motives.